Ivermectin dan Covid-19: Sebuah Tinjauan Literatur - Henry Wijaya; Niluh Ayu Sri Saraswati; Devinqa Adhimah Amanda (Majalah Kesehatan Indonesia, 2021)
Coronavirus disease (COVID-19) is an infectious disease that has been declared a pandemic by WHO and has become a case of a health emergency in the world. This disease is caused by the novel coronavirus (SARS-CoV-2) which was first identified in China. Until now, various studies have been conducted to find the most effective drug in eradicating this pandemic. Ivermectin, an anti-parasitic drug, is known to have antiviral properties by inhibiting the entry of viruses into the cells. On this basis, Ivermectin is believed to be capable of being one of the COVID-19 therapies. This literature review is a review of emerging cases, namely COVID-19 and its relation to Ivermectin, using the published data obtained through Google Scholar, PubMed, and WHO dataIvermectin, a parasitic agent that has been approved by the FDA, was able to prevent viral proteins from entering the host cell nucleus. Ivermectin was also shown to be able to accelerate viral clearance in the body compared to the placebo group and show a significant reduction in CRP and LDH levels. Patients receiving ivermectin also showed a lower incidence of respiratory distress and a shorter duration of hospitalization. The administration of ivermectin as a COVID-19 drug can have a positive impact on patients both clinically and in the laboratory. ABSTRAK: Penyakit coronavirus (COVID-19) adalah suatu penyakit infeksi yang telah diumumkan sebagai suatu pandemi oleh WHO dan menjadi kasus gawat darurat kesehatan di dunia. Penyakit ini disebabkan oleh novel coronavirus (SARS-CoV-2) yang pertama kali di China. Hingga saat ini berbagai penelitian telah dijalankan untuk menemukan obat yang paling efektif dalam membasmi pandemi ini. Ivermectin, obat anti parasit, diketahui memiliki sifat anti virus dengan cara menghambat proses masuknya virus ke dalam sel tubuh. Dengan dasar ini, Ivermectin dipercayai mampu menjadi salah satu terapi COVID-19. Tinjauan literatur ini merupakan sebuah tinjauan kasus emerging yakni COVID-19 dan kaitannya dengan Ivermectin, dimana sumber tulisan didapatkan melalui data google cendekia, PubMed, dan WHO. Ivermectin, suatu agen parasit yang telah disetujui oleh FDA, mampu mencegah protein virus masuk ke dalam nukleus sel host. Ivermectin juga dibuktikan mampu mempercepat klirens virus di dalam tubuh dibandingkan dengan kelompok placebo dan menunjukkan penurunan yang signifikan pada kadar CRP dan LDH. Pasien-pasien yang mendapatkan ivermectin juga menunjukkan angka kejadian distres nafas yang lebih rendah dan durasi rawat inap yang lebih singkat. Pemberian ivermectin sebagai obat COVID-19 mampu memberikan dampak yang positif kepada pasien baik secara klinis maupun laboratorium.